Strategi Komunikasi Podcast Lewat Tengah Malam di Makassar dalam Menarik Pendengar - Pratiwi, Indah Pratiwi; Meisuki, Nawang Wulan (Journal of Communication Sciences (JCoS), 2023)
The “Lewat Tengah Malam” is a horror and crime genre podcast which is one of the popular podcasts in Makassar. The aim of this research is to determine the communication strategy of the “Lewat Tengah Malam” Podcast in Makassar, as well as the supporting and inhibiting factors in attracting listeners. The type of research is qualitative research with descriptive research type. Data collection techniques through interviews, documentation and observation with three informants. The research results show that the communication strategy to attract listeners' interest are unique, interesting and high-quality podcast content, ease of listening, and credible podcasters. This research also found that there are several supporting factors in the communication strategy of the “Lewat Tengah Malam” Podcast, including support from agencies, the use of social media, and the availability of adequate facilities. Meanwhile, the inhibiting factor is that there is a similarity in the content of the same story, but this can be overcome by presenting the story from a different point of view.